Henry and Beezus - Cleary, Beverly; Dockray, Tracy (New York : HarperTrophy, 2007)
Henry Huggins, his dog Ribsy, and his friend Beezus, busy themselves with trying to earn enough money for Henry to buy a bicycle.
Booklist.
4.7
3-6
Keywords: Bicycles -- Juvenile fiction; Dogs -- Juvenile fiction; Friendship -- Juvenile fiction; Bicycles and bicycling -- Fiction; Dogs -- Fiction; Friendship -- Fiction; Bicycles -- Fiction; Dogs -- Fiction; Friendship -- Fiction